Creating an Environment for Nuclear Disarmament (CEND): a good faith, effective measure pursuant to Article VI NPT or empty gesturing?. Issue 2 (December 2020) - Evans, Christopher P
Abstract : It has been 50 years since the adoption of the Treaty on the Non-Proliferation of Nuclear Weapons (NPT), which established the obligation upon all States Parties to work towards nuclear disarmament under Article VI. Yet, despite extensive reductions in nuclear weapons stockpiles since the Cold War peaks, nuclear arms control and disarmament efforts are currently in disarray. After the Intermediate-Range Nuclear Forces Treaty was terminated in 2019, the New Strategic Arms Reduction Treaty remains as the only bilateral limitation on United States (US) and Russian nuclear forces in operation and is due to expire in February 2021. The US has justified its limited nuclear disarmament progress on the premise that the current international security environment is not conducive to further nuclear disarmament. Instead, the US has recently promoted a new initiative called Creating an Environment for Nuclear Disarmament (CEND). The initiative aims to provide a platform for all States to engage in constructive dialogue to identify ways to improve the international security environment, which make nuclear deterrence necessary while addressing the hurdles that currently impede progress towards nuclear disarmament. Significantly, the US regards CEND as an 'effective measure' and an illustration of its commitment towards disarmament under Article VI. This article seeks to address the US claim that CEND represents a good faith, effective measure towards nuclear disarmament pursuant to Article VI. This will revisit existing doctrinal interpretative debates concerning the obligation under Article VI, particularly the requirements that negotiations and measures be adopted in good faith, and what constitutes an effective measure towards nuclear disarmament. The discussion will then determine whether the CEND initiative itself can be considered a good faith, effective measure towards nuclear disarmament, by considering its purpose, origins and implementation, and actions of the US.